Intercostal Nerve Transfer to Neurotize the Musculocutaneous Nerve after Traumatic Brachial Plexus Avulsion: A Comparison of Two, Three, and Four Nerve Transfers - Xiao, Chengwei; Lao, Jie; Wang, Tao; Zhao, Xin; Liu, Jingbo; Gu, Yudong (Journal of Reconstructive Microsurgery, 2014)
The purpose of this study was to compare the outcomes of different numbers of intercostal nerve (ICN) transfers for elbow flexion and to determine whether age, body mass index (BMI), type of injury, and preoperative delay influence the outcomes. From 2004 to 2010, 32 (30 included) consecutive patients underwent ICN transfer to the musculocutaneous nerve following brachial plexus injury. Elbow flexion strength was evaluated according to the British Medical Research Council (BMRC) grading system. Of nine patients who received two ICN transfers, six (66.7%) recovered with useful elbow flexion compared with 14 of 17 (82.4%) patients who received three ICN transfers. Of the four patients with four ICN transfers, three (75%) achieved useful recovery. Statistical analysis showed no significant difference. There is no significant difference among the outcomes of two, three, and four ICN transfers to the musculocutaneous nerve. Two ICN transfers are sufficient for useful recovery of elbow flexion. Younger patients achieve better results.
Keywords: brachial plexus injury; intercostal nerve; nerve transfer; musculocutaneous nerve; elbow flexion